2012
DOI: 10.1016/j.devcel.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Stem Cells by Intersecting Gradients of Long-Range Niche Signals

Abstract: SUMMARY We have used Drosophila ovarian Follicle Stem Cells (FSCs) to study how stem cells are regulated by external signals and draw three main conclusions. First, the spatial definition of supportive niche positions for FSCs depends on gradients of Hh and JAK-STAT pathway ligands, which emanate from opposite, distant sites. FSC position may be further refined by a preference for low-level Wnt signaling. Second, hyperactivity of supportive signaling pathways can compensate for the absence of the otherwise ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
113
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(133 citation statements)
references
References 34 publications
19
113
1
Order By: Relevance
“…This makes it challenging to pinpoint whether defects observed in integrin mutants are due to loss of function within the FSC itself (O'Reilly et al 2008) or whether defective signals from clonally identical integrin-mutant daughter cells influence FSC function (Vied et al 2012). A third possibility is that the marked cells observed are not FSCs but instead are differentiated daughter cells that cannot effectively incorporate into the developing epithelium and are gradually pushed toward the anterior.…”
Section: Integrins Provide Directional Information To Fscs During Celmentioning
confidence: 95%
See 2 more Smart Citations
“…This makes it challenging to pinpoint whether defects observed in integrin mutants are due to loss of function within the FSC itself (O'Reilly et al 2008) or whether defective signals from clonally identical integrin-mutant daughter cells influence FSC function (Vied et al 2012). A third possibility is that the marked cells observed are not FSCs but instead are differentiated daughter cells that cannot effectively incorporate into the developing epithelium and are gradually pushed toward the anterior.…”
Section: Integrins Provide Directional Information To Fscs During Celmentioning
confidence: 95%
“…Recently, it was shown that differentiated daughter cells influence FSCs via a signaling feedback mechanism (Vied et al 2012). This makes it challenging to pinpoint whether defects observed in integrin mutants are due to loss of function within the FSC itself (O'Reilly et al 2008) or whether defective signals from clonally identical integrin-mutant daughter cells influence FSC function (Vied et al 2012).…”
Section: Integrins Provide Directional Information To Fscs During Celmentioning
confidence: 99%
See 1 more Smart Citation
“…Follicle cells continue to divide to generate ,30 epithelial cells, which are sufficient for the formation of an epithelial monolayer covering the cyst when it exits the germarium (Nystul and Spradling, 2010). Although it has been shown that Hedgehog, Wnt, BMP and JAK/STAT signalling pathways control division in the follicle stem cell niche (Forbes et al, 1996;Zhang and Kalderon, 2000;Zhang and Kalderon, 2001;Song and Xie, 2003;Kirilly et al, 2005;Vied et al, 2012), it is unclear how follicle cell proliferation is controlled outside of the niche.…”
Section: Introductionmentioning
confidence: 99%
“…Two FSCs are located halfway down the germarium at the junction of regions 2A and 2B (Figure 1; Margolis and Spradling 1995;Nystul and Spradling 2007). Their proliferation depends on signals received from regions located both anterior and posterior to the FSCs (Sahai-Hernandez et al 2012;Vied et al 2012;Sahai-Hernandez and Nystul 2013). Similar to GSCs, FSCs divide asymmetrically, giving rise to one daughter cell that remains in the niche as a FSC, and a second daughter cell that exits the niche and begins to differentiate (Morrison and Spradling 2008).…”
mentioning
confidence: 99%